An Analysis of Senior High School Students' Mathematical Communication Ability Based on Self-Efficacy and Gender - Nurjanah, Rohmah; Jusra, Hella (Universitas Islam Negeri Raden Intan Lampung, 2022)
Mathematical communication skills are one of the skills that students need in the 21st century. This study aimed to describe the mathematical communication skills of high school students based on self-efficacy and gender. The research method used is descriptive qualitative. Six subjects from 103 students of class XI-MIPA were determined based on the categories of self-efficacy and gender. The results of this study are (1) students who have high self-efficacy can achieve all indicators of mathematical communication skills, male students are better than female students; (2) students who have moderate self-efficacy can achieve two indicators of mathematical communication skills, female students are better than male students; and (3) students who have low self-efficacy only achieve one indicator of mathematical communication skills, female students are better than male students. It can be concluded that there are differences in the mathematical communication skills of high school students based on the level of self-efficacy. In addition, there are differences in mathematical communication skills between male and female students. Educators can use this research as a reference in choosing the appropriate learning model.